Changes in macrophage function after rituximab treatment in patients with rheumatoid arthritis. Issue 6 (5th December 2006) - Toubi, E; Kessel, A; Slobodin, G; Boulman, N; Pavlotzky, E; Zisman, D; Rozenbaum, M; Rosner, I
Abstract : Objective: To assess changes in macrophage phenotype and function after rituximab-induced B cell depletion in patients with rheumatoid arthritis (RA). Methods: 10 patients with RA were treated with rituximab, achieving significant B cell depletion 4 months later. Clinical improvement, rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP) antibodies, mRNA of B cell activating factor (BAFF), interleukin (IL) 10 and CD86 in human monocyte-derived macrophages (HMDMs) and tumour necrosis factor α (TNFα) secretion from cultured HMDMs were assessed at baseline and after the depletion. Results: A clinical response of American College of Rheumatology (ACR) 50% improvement was noted in six patients, and another two patients responded with moderate improvement, equivalent to ACR 20–50% improvements. RF and anti-CCP antibodies were positive at baseline in seven of ten patients. RF disappeared or declined in six patients 4 months after treatment, correlating with clinical improvement. By contrast, anti-CCP remained unchanged in six patients. After rituximab treatment, and in association with clinical improvement, BAFF, IL10 and CD86 mRNA expression in HMDM were significantly upregulated compared with values at baseline. A significant decrease in TNFα in the supernatant of cultured HMDM was also noted. Conclusions: In addition to B cell depletion and attenuation in some of the specific autoantibodies, clinical improvement in rituximab-treated patients with RA occurred in association with changes in macrophage function.